2006
DOI: 10.1002/pmic.200600420
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the utility of SELDI-TOF and model averaging for serum proteomic biomarker discovery

Abstract: The SELDI-TOF technique was used to profile serum proteins from Type 1 diabetes (T1D) patients and healthy autoantibody-negative (AbN) controls. Univariate and multivariate analyses were performed to identify putative biomarkers for T1D and to assess the reproducibility of the SELDI technique. We found 146 protein/peptide peaks (581 total peaks discovered) in human serum showing statistical differences in expression levels between T1D patients and controls, with 84% of these peaks showing technical replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…An additional problem is the less-effective ionization in the high molecular range resulting with apparently lower sensitivity of the instrument for large proteins. After improvement of both the hardware and software, and thorough investigations of sample storage and preparation, SELDI-TOF MS is again being more frequently used [16][17][18][19]. The big advantage of the SELDI-TOF technology is the simple automation of sample preparation and the measurement process that enables its use for high-throughput screening, which is necessary when dealing with large sample numbers during the biomarker discovery process.…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem is the less-effective ionization in the high molecular range resulting with apparently lower sensitivity of the instrument for large proteins. After improvement of both the hardware and software, and thorough investigations of sample storage and preparation, SELDI-TOF MS is again being more frequently used [16][17][18][19]. The big advantage of the SELDI-TOF technology is the simple automation of sample preparation and the measurement process that enables its use for high-throughput screening, which is necessary when dealing with large sample numbers during the biomarker discovery process.…”
Section: Discussionmentioning
confidence: 99%
“…The easy accessibility of blood in contrast to pancreatic islets makes it attractive to study changes of other blood-borne proteins also, which may be related to the progression of the disease. With the development of different methodologies capable of simultaneously measuring large numbers of proteins present in biological samples, blood protein profiling has become an important area for studying the pathophysiology of type 2 diabetes [12][13][14]. We have used the SELDI-platform, which uses chemically defined surfaces to capture proteins [15].…”
Section: Discussionmentioning
confidence: 99%
“…The high technical replication of peaks by SELDI-TOF showed the reliability of this method, and the results obtained in this study confirmed the best condition reported by Purohit's group. 20 According to China's national diagnostic standard for pneumoconiosis (enacted in 2002), the diagnosis of silicosis mainly depends on occupational history and radiological evidence. This definitely lags behind biochemical change and tissue biopsy, while the invasive nature of biopsy limited its application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%